Re-Intubation among critical care patients: a scoping review - Jamaludin, Thandar Soe Sumaiyah; Nurumal, Mohd. Said; Syaziman, Nur Syila Syahida; Suhaimi, Syuhada; Che Hasan, Muhammad Kamil (IIUM Press, 2021)
Objective: This paper aimed to identify relevant literature about what are the factors that contributing to the re-intubation and current intervention to overcome it among critical care patients. Methods: A scoping review was carried out with the 17 articles which publish with the year 2010 to 2021. The literature search was systematically done by using PRISMA flow diagram. The quality assessment was conducted by using Effective Public Health Practice Project (EPHPP) assessment tool and the authors applied inter-rater reliability for the included articles. Results: Four themes were emerged in this scoping review. Those were the criteria for extubation, factors of extubation failure and re-intubation, medical conditions associated with re-intubation, and intervention to reduce reintubation rate among critical care patients. Conclusion: The rate of re-intubation among critical care patients can be reduced when protective measures take place properly. Those are the use of non-invasive ventilation in between successful spontaneous breathing trials and extubation, the proper usage of analgesics and sedatives during extubation and monitoring the indicators like blood urea nitrogen and central venous pressure